Exploring the Impact of Skin Tone Perception on Race-Related Outcomes and Familial Functioning Among African American Youth: Implications for African-Centered Interventions. Issue 4 (October 2021) - Lateef, Husain; Smyth, Heather; Williams, Maya; Gale, Adrian; Williams, Ed-Dee; Boyd, Donte; Howard Howell, Tyriesa; Williams-Butler, Abigail
Racism and its ramifications are salient societal-level factors that detrimentally affect African American youth and families. Few studies have investigated how African American youth experience discrimination within families and society and colorism's impact on racial identity, despite extensive racial discrimination research. We assessed whether the perceptions of African American youth of their skin tone affected their racial identity, familial functioning, and everyday discrimination, using the National Survey of American Life–Adolescent Supplement data. We found no significant relationships among skin tone perception, racial identity, familial functioning, or everyday experiences of discrimination. Conversely, age and gender differences were significant predictors of racial identity, family functioning, and discrimination reports. We discuss the theoretical and practical implications of these findings for social work practice.